Biophysical properties of microvascular endothelium: Requirements for initiating and conducting electrical signals. (9th February 2018) - Kapela, Adam; Behringer, Erik J.; Segal, Steven S.; Tsoukias, Nikolaos M.
Abstract: Objective: Electrical signaling along the endothelium underlies spreading vasodilation and blood flow control. We use mathematical modeling to determine the electrical properties of the endothelium and gain insight into the biophysical determinants of electrical conduction. Methods: Electrical conduction data along endothelial tubes (40 μm wide, 2.5 mm long) isolated from mouse skeletal muscle resistance arteries were analyzed using cable equations and a multicellular computational model. Results: Responses to intracellular current injection attenuate with an axial length constant (λ) of 1.2‐1.4 mm. Data were fitted to estimate the axial ( r a ; 10.7 MΩ/mm) and membrane ( r m ; 14.5 MΩ∙mm) resistivities, EC membrane resistance ( R m ; 12 GΩ), and EC‐EC coupling resistance ( R gj ; 4.5 MΩ) and predict that stimulation of ≥30 neighboring ECs is required to elicit 1 mV of hyperpolarization at distance = 2.5 mm. Opening Ca 2+ ‐activated K + channels (KC a ) along the endothelium reduced λ by up to 55%. Conclusions: High R m makes the endothelium sensitive to electrical stimuli and able to conduct these signals effectively. Whereas the activation of a group of ECs is required to initiate physiologically relevant hyperpolarization, this requirement is increased by myoendothelial coupling and KC a activation along the endothelium inhibits conduction by dissipating electrical signals.